Managing the work of living with heart failure: a qualitative study using the cumulative complexity model from Southeastern Minnesota - Dawn Finnie; Víctor M Montori; Jamie Smith; Margaret M Redfield; Jill M Killian; Nathan Shippee; Shannon Dunlay (BMJ Open)
Objective Patients with heart failure (HF) perform a variety of self-care activities to control symptoms and minimise the risk of HF decompensations. The objective of this study was to understand how patients build capacity and manage the work of living with HF.Design A qualitative study using semi-structured telephone interviews. The interview guide was informed by the Cumulative Complexity Model, a conceptual framework that focuses on a patient’s workload and their capacity to manage that work. Interview transcripts were analysed using a mixed inductive and deductive coding approach with organisation into larger thematic categories.Setting Southeastern Minnesota USA (11 counties) with capture of data from local community healthcare providers under the auspices of the Rochester Epidemiology Project.Participants Intentional sampling of local patients with HF (n=24, median age 69.5 years, 54% women, 63% rural, 54% preserved ejection fraction) who reported high treatment burden and/ or poor health status on a questionnaire.Results Three major themes emerged: using capacity to manage workload, disruptions resulting in workload exceeding capacity and regaining workload-capacity balance. Participants described routinising the daily tasks associated with living with HF to minimise the associated burden and identified disruptions to their routines, including hospitalisations, emergency room visits, worsening health status and changes in healthcare access. To accommodate disruptions and regain workload-capacity balance, participants decreased workload and/or transferred tasks to others to maximise capacity.Conclusions Participants with HF described managing patient workload in times of stable health, but they sometimes struggled to accommodate disruptions and worsening health status. These findings can inform the design of interventions to minimise workload, maximise capacity and improve quality of life for patients with HF.